The moderating role of food cravings in the relationship between weight suppression and eating disorder psychopathology in college students - Garcia, Susana Cruz; Hormes, Julia M. (Frontiers in Psychology, 2024)
Weight suppression (WS), the difference between one’s current and highest adult weight, is predictive of eating-related pathology across diagnostic categories and poor eating disorder treatment outcomes, but findings from non-clinical samples have been mixed. Cravings are strong urges for specific foods that are subjectively difficult to resist. Food cravings are now widely conceptualized as cognitive-affective states characterized by intrusive thoughts that are perceived as distressing and can interfere with adaptive functioning. Food cravings are known antecedents of binge eating, but little is known about how they interact with WS. We examined the obsessive-compulsive aspects of food cravings as potential moderators of the association between WS and eating disorder symptoms in general, and binge eating specifically in a cross-sectional study of college students. Participants (n=144, 60.4% female) self-reported their height and current and past highest adult weight and completed the Binge Eating Scale (BES), Eating Disorder Examination-Questionnaire (EDE-Q), and Obsessive Compulsive Eating Scale (OCES). Main and interactive effects of WS and OCES scores on EDE-Q global and BES scores were examined in regression models. There were significant main effects of OCES scores on overall eating disorder symptom severity as well as binge frequency, with those endorsing more craving-related intrusive thoughts and compulsive urges engaging in maladaptive behaviors more frequently. WS alone did not consistently cross-sectionally predict eating disorder psychopathology. Findings suggest that food cravings are significantly associated with disordered eating symptoms and specifically binge eating frequency and should be accounted for in future research on WS in clinical and non-clinical samples.